Pengembangan Chat Bot pada CoMa untuk memberikan motivasi kepada pengguna menggunakan AIML - Bestralaga Rusmarasy; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ease of access and teaching-learning activities in e-Learning raises a new problem, where there are some students who found a difficulties to do a task in e-Learning and lack of motivation in doing the task. With the Code Maniac e-Learning website was help students in the learning process, but haven't been able built the students motivation. So in this study will enhance CodeManiac e-Learning website with the addition of chatbot to provide motivation to users and actively capture user behavior and give a messages based on user behavior. In this study writer used AIML. AIML itself is subset of XML. Like XML, AIML here as the language used to construct chatbot logic which contains a set of patterns and responses that can be used by chatbot to track answers every sentence given. With this implementation has been motivated CodeManiac users feels by the chatbot who can interact with users and actively captures user behavior. In final step on the enhancement of codemaniac has been tested with whitebox testing, blackbox testing and usability testing with each score 100% valid, 100% valid and 88%.